2020
DOI: 10.4314/iijikm.v11i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Use of Electronic Information Resources by Students of College of Health Sciences in Olabisi Onabanjo University, Nigeria

Abstract: The study examined awareness and use of electronic Information Resources (EIR) among students in College of Health Sciences, Sagamu, Nigeria. The objectives were to establish types of resources available, determine level of awareness, extent of the use of e-resources and problems faced. Descriptive survey design with real-time observation method was used to collect data using a structured questionnaire. The population comprised 2000 students in the College while purposive sampling technique was used to select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…It is therefore vital for librarians to create awareness concerning the library and its resources. This view is in line with the views of [15] whose study revealed that students are not aware of the resources in the library. Lack of awareness of availability of information resources tends to prevent students from utilizing the information resources made available in the library.…”
Section: Awareness Of Availability Of Information Resources and Utili...supporting
confidence: 85%
See 2 more Smart Citations
“…It is therefore vital for librarians to create awareness concerning the library and its resources. This view is in line with the views of [15] whose study revealed that students are not aware of the resources in the library. Lack of awareness of availability of information resources tends to prevent students from utilizing the information resources made available in the library.…”
Section: Awareness Of Availability Of Information Resources and Utili...supporting
confidence: 85%
“…They have to interact with tangible and non-tangible information resources to ensure their academic excellence. Stressing the importance and benefits of utilizing information resources in the library, [15] observed that students are either not aware and or not making optimum use of these vital resources. She went ahead to note that, of what benefits are resources when they are not utilized for the purpose for which they are acquired?…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Internet resources, electronic resources, e-journals, and online information resources are also included (Lee, 2012). These items need researcher access to a computer via desktop or mobile devices in a library or at home (Osinulu, 2020). Researchers can use online research resources (ORRs) to review literature, instrument preparation, data collecting, and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of navigating through electronic resources continues to be a challenge for users (Enakrire and Onyanania, 2007). Some researchers have looked into how people are aware of and use electronic information resources (Osinulu, 2020), E-resources (Ansari, 2020), and internet resources and services (Osinulu, 2020). According to Suleiman and Joshua ( 2019), these resources were seldom used.…”
Section: Introductionmentioning
confidence: 99%